The parametric HFGMC micromechanical model for soft UHMWPE laminated composites. (January 2020) - Meshi, Ido; Levi-Sasson, Aviad; Breiman, Uri; Haj-Ali, Rami
Abstract: The 3D parametric High-Fidelity-Generalized-Method-of-Cells (HFGMC) micromechanical model was used to predict the mechanical tensile behavior of ultra-high-molecular-weight-polyethylene (UHMWPE) cross-ply laminated composite (Dyneema®). The composite microstructure was obtained from optical microscope images and was digitized using CAD software. Two configurations of 3D representative-volume-elements (RVE)s were constructed and analyzed to demonstrate the capability of the HFGMC in predicting the effective behavior of UHMWPE laminated composites. The elastic properties of both constituents (fiber and matrix) were obtained from published experimental data and from in-house experiments. Linear and nonlinear constitutive laws were applied for the constituents for comparison. The parametric HFGMC predictions for the overall mechanical properties were compared with extensive tensile experiments. The nonlinear behavior under in-plane shear was also examined in order to evaluate the effect of the proposed RVE configurations for the laminated composite. The parametric HFGMC (PHFGMC) is formulated using the virtual work for both the global and local fields. This allows the development of a new incremental-iterative nonlinear solution scheme. Special periodicity constraints are proposed for the special, yet prevalent case, of non-periodic RVE mesh. The parametric HFGMC micromechanical model is shown to be capable to simulate the nonlinear behavior of soft composites. This model can be generalized for rate dependent constituents.